Survival Strategy of Rubber Farmers When There is a Decline in Rubber Prices in Ampung Padang Village, Batang Natal District, Mandailing Natal Regency - Aina Zahwa; Sismudjito Sismudjito; R Hamdani Harahap (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This research is entitled "Survival strategy of rubber farmers when there is a decline in rubber prices in Ampung Padang Village, Batang Natal District, Mandailing Natal Regency". The location of this study was chosen because the majority of the population in Ampung Padang Village make a living as rubber farmers. This study aims to determine the survival strategy of rubber farmers when there is a decline in rubber prices in Ampung Padang Village, Batang Natal District, Mandailing Natal Regency and to find out the forms of strategies that rubber farmers use when rubber prices decline. The research method used is a descriptive study method with a qualitative approach. Data collection techniques were carried out by means of observation, in-depth interviews, and literature study. The informants in this study were rubber farmers in Ampung Padang Village, Batang Natal District, Mandailing Natal Regency. Data analysis used is data reduction, data presentation, and drawing conclusions or verification. The results showed that there were three strategies that rubber farmers used to survive, namely: active strategy, passive strategy, and network strategy. The active strategy carried out by rubber farmers is to look for side jobs, join family members to work and optimize all available resources. The passive strategy carried out by rubber farmers is to apply a frugal lifestyle and reduce family expenses. The network strategy used by rubber farmers is to ask for help from the social networks they have, both formal and informal networks.